Developing Multimedia Based Materials to Teach Listening Comprehension - destina kasriyati (ELT-Lectura, 2018)
The aim of the study were: to describe multimedia based materials availaible, to find out what multimedia based materials needed, to develop multimedia based materials, and to describe the effectiveness of the multimedia based materials developed. The study used Research and Development (R&D) design which was used to develop products and measure the effectiveness of development product proposed by Borg and Gall (2007).The findings of study were: firstly, the researcher did not find the multimedia materials as teaching and learning sources at school, because the teacher used text book and teacher talk in listening activity. Secondly, the result of prelimenary research showed that in English teaching and learning process need a multimedia based materials as learning media to support listening activity in the language laboratory. Thirdly, multimedia has been developed based on the students’ need and interest, beside that developing multimedia also based on the current curriculum (2013 curriculum). The last, the result of pre-test and post-test that multimedia was effective for learning listening and it can be applied teaching and learning process at seven grade students of state junior high school thirteen Semarang. The final product of this study was a package of interactive CD-ROM for learning listening.